REPRESENTASI TOKOH DALAM KUMPULAN CERPEN SAGRA KARYA OKA RUSMINI - Wina Hendrayani Putu; Gde Artawan; I Nyoman Yasa (Universitas Nahdlatul Wathan Mataram, 2023)
This research is a qualitative descriptive study aimed at understanding the representation of character identity in the collection of short stories titled